An Error Analysis in Using Past Tense in Writing Recount Text at the Tenth-Grade Students of MA Nurussalam Tetebatu in Academic Year 2024/2025 - Ernawati, Ernawati; Wardana, Lalu Ali; Suryaningsih, Hartati (Jurnal Ilmiah Profesi Pendidikan, 2025)
This thesis investigates the types and dominant errors made by tenth-grade students of MA Nurussalam Tetebatu in the academic year 2024/2025 when writing recount texts, specifically focusing on their use of the past tense. Writing is identified as a challenging skill for English as a Foreign Language (EFL) students in Indonesia, often leading to grammatical errors, particularly in recount texts which necessitate the use of past tense to retell events. The study categorized errors into four main types: omission, addition, misformation (selection), and misordering. Employing a descriptive quantitative research design, the research involved a sample of 62 students from classes X.2 and X.4, selected using cluster sampling from a total population of 130 tenth-grade students. Data was collected through a writing test where students composed a recount text titled "My Past Holiday". The analysis involved identifying, describing, and explaining the observed errors to understand their underlying causes, such as first language interference or a lack of conceptual understanding. The findings revealed that misformation was the most dominant error type, accounting for 53.85% of all errors. This research provides valuable insights into the persistent challenges students face in mastering English grammar, particularly past tense forms, and aims to serve as a foundation for improving teaching strategies for writing recount texts.